Obsessive-compulsive symptoms and obsessive-compulsive disorder in adolescents: a population-based study - Analise de Souza Vivan; Lidiane Rodrigues; Guilherme Wendt; Mônica Giaretton Bicca; Daniela Tusi Braga; Aristides Volpato Cordioli (Brazilian Journal of Psychiatry, 2014)
Objectives: To estimate the prevalence of obsessive-compulsive symptoms (OCS) and disorder (OCD) among adolescents and to describe OCD characteristics according to gender. Methods: Participants were selected by cluster sampling at seven high-schools in southern Brazil. In the first stage, 2,323 students were screened for OCS; in the second stage, adolescents scoring ≥ 21 on the OCI-R scale were individually interviewed. OCD diagnosis was established using a semi-structured interview (Schedule for Affective Disorders and Schizophrenia for School Aged Children: Present and Lifetime Version - K-SADS-PL). Results: The past-month estimated prevalence of OCS was 18.3%, and the point estimated prevalence of OCD, 3.3%. Girls showed higher scores (OCS: 24.8 vs. 14.4%; OCD: 4.9 vs. 1.4%; p < 0.001). Only 9.3% of OCD adolescents had been diagnosed and 6.7% received treatment. The most frequent/severe DY-BOCS dimensions were miscellaneous (86.7%; mean score 6.3±3.8) and symmetry (85.3%; 5.9±3.8). Female OCD adolescents predominantly showed depression (p = 0.032), and male adolescents, tic disorders (p = 0.006). Conclusions: OCD is underdiagnosed in adolescents, and few are treated. Future studies should investigate the relationship between OCS and the onset of OCD.